Silicon regulation of manganese homeostasis in plants: mechanisms and future prospective - Hailai, Yuebu; Liu, Yuan; Yang, Zhengming; Li, Ying; Feng, Jingqiu; Li, Wenbing; Sheng, Huachun (Frontiers in Plant Science, 2024)
Manganese (Mn), a plant micronutrient element, is an important component of metalloprotein involved in multiple metabolic processes, such as photosynthesis and scavenging reactive oxygen species (ROS). Its disorder (deficiency or excess) affects the Mn-dependent metabolic processes and subsequent growth and development of plants. The beneficial element of Si has a variety of applications in agricultural fields for plant adaptation to various environmental stresses, including Mn disorder. The probable mechanisms for Si alleviation of Mn toxicity in plants are summarized as follows: (1) Si alters the rhizosphere acidification, root exudates and microorganisms to decrease the bioavailability of Mn in the rhizosphere; (2) Si down-regulates Mn transporter gene and reinforces the apoplastic barriers for inhibiting the Mn uptake and translocation; and (3) Si promotes the Mn deposition onto cell wall and Mn compartmentation into vacuole. Under Mn-deficient conditions, the probable mechanisms for Si promotion of Mn absorption in some plants remain an open question. Moreover, scavenging ROS is a common mechanism for Si alleviating Mn disorder. This minireview highlights the current understanding and future perspectives of Si regulation of manganese homeostasis in plants.